Utilization of TVUS and fFN Screening, Antenatal Steroids Use and Risk of Preterm Delivery [11H]. (May 2018) - Lauder, Jhenette; Shen, Xian; Petrilla, Allison; Sullivan, Erin; Troeger, Kathleen; Sciscione, Anthony
Abstract : INTRODUCTION: This study measured use of fetal fibronectin (fFN) testing and transvaginal ultrasound (TVUS) among women with symptomatic preterm labor (PTL) and evaluated use of antenatal steroids and time to infant delivery. METHODS: A cohort of pregnant women with symptomatic PTL in 2012-2016 was identified; exclusion criteria included: premature rupture of membranes, pre-eclampsia, viral infection, and no record of delivery. Four patient groups were formed based on receipt of the combination of fFN testing and TVUS: fFN only, TVUS only, fFN and TVUS, neither fFN nor TVUS. Kaplan-Meier analysis and Cox Proportional Hazard model were performed to assess time to delivery following the PTL assessment. RESULTS: A total of 94, 343 patients were included in the analysis; 6.7% patients received fFN test only, 13.3% received TVUS only, 3.2% received both fFN test and TVUS, and 76.8% received neither test. Antenatal steroids utilization ranged from 1.0% in the group receiving neither test to 7.9% in the group receiving both tests. The average time to delivery was shortest for patients who received neither test (12.1 days), followed by TVUS only (16.3 days), fFN only (31.2 days) and the fFN and TVUS (31.4 days) group. The adjusted risk for infant delivery within 7 days was approximately 50% lower for women who received fFN test and 10% lower for the TVUS only group compared to those who received neither test. CONCLUSION: Less than one in five eligible patients triaged for symptomatic PTL received TVUS or fFN. Among those who received fFN testing, a longer interval to birth was observed.